Why natural selection leads to complexity - Benzon, William L.; Hays, David G. (1990)
While science has accepted biological evolution through natural selection, there is no generally agreed explanation for why evolution leads to ever more complex organisms. Evolution yields organismic complexity because the universe is, in its very fabric, inherently complex, as suggested by Ilya Prigogine's work on dissipative structures. Because the universe is complex, increments in organismic complexity yield survival benefits: (1) more efficient extraction of energy and matter, (2) more flexible response to vicissitudes, (3) more effective search. J.J. Gibson's ecological psychology provides a clue to the advantages of sophisticated information processing while the lore of computational theory suggests that a complex computer is needed efficiently to perform complex computations (i.e. sophisticated information processing).